Case Report: A Case With Philadelphia Chromosome Positive T-Cell Lymphoblastic Lymphoma and a Review of Literature - Li, Xuewei; Ping, Nana; Wang, Yong; Xu, Xiaoyu; Gao, Lijuan; Zeng, Zhao; Zhang, Ling; Zhang, Zhibo; Xie, Yiyu; Ruan, Changgeng; Wu, Depei; Jin, Zhengming; et al. (Frontiers in Oncology, 2021)
Philadelphia chromosome positive (Ph+) in T-lineage acute lymphoproliferative tumors is a rare event in both children and adults. In particular, it has not been reported in T-cell lymphoblastic lymphoma(T-LBL) yet. Here, we describe a patient with Ph+ T-LBL for both cytogenetic abnormality and BCR-ABL1 fusion transcript. Moreover, we review the published cases of Ph+ T-cell acute lymphoblastic leukemia (T-ALL) in the literature and summarize their clinical characteristics, management and prognosis.